2020
DOI: 10.1542/hpeds.2019-0290
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Massive and Submassive Pulmonary Embolism: A Single-Center Experience

Abstract: To describe and compare patient and event characteristics and outcomes in pediatric massive pulmonary embolism (MPE) and submassive pulmonary embolism (SMPE). METHODS: A retrospective cohort study at a quaternary-care pediatric hospital was conducted. Patients age ,19 years with MPE (acute pulmonary embolism [PE] with cardiac arrest, hypotension, or compensated shock due to PE) or SMPE (right ventricular strain due to acute PE) between January 1997 and June 2019 were included. RESULTS: Thirty-three patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…This was followed by full text review of 11 articles, with the nal involvement of six studies that were eligible according to our inclusion criteria (PRISMA; Figure 1) The six articles reported a total of 258 patients with massive, submissive, or nonmassive pulmonary embolisms Table 1. Three of the articles included were retrospective cohort studies [3,4,11], while the other three were case series [8, 12,13]. Patient baseline chacartesics and risk factors are demonstrated in detail in Tables 2 & 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was followed by full text review of 11 articles, with the nal involvement of six studies that were eligible according to our inclusion criteria (PRISMA; Figure 1) The six articles reported a total of 258 patients with massive, submissive, or nonmassive pulmonary embolisms Table 1. Three of the articles included were retrospective cohort studies [3,4,11], while the other three were case series [8, 12,13]. Patient baseline chacartesics and risk factors are demonstrated in detail in Tables 2 & 3.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the prognosis varied among patients with PE. Ross et al reported that survivors had excellent outcomes with no sequelae from PE or recurrence of PE during a median follow-up of 16 months [3]. Pelland-Marcotte et al observed a median follow-up period of 2.4 years, during which 19% of patients experienced unfavorable outcomes related to PE [11].…”
Section: Prognosis and Mortalitymentioning
confidence: 99%
“…5 However, multiple recent studies have concluded that certain risk factors are associated with worse outcomes in children, including CVC placement, immobility, and critical or complex chronic illness. 5,[7][8][9][10][11] Carpenter et al 1 noted that African American and Hispanic patients were significantly more likely to experience recurrent PE than white patients, and it is currently unknown what factors influence recurrence rates in non-white populations.…”
Section: Introductionmentioning
confidence: 99%
“…Although some previous studies have attempted to describe risk factors for PE in children, the majority of these analyses are limited by small sample sizes or their single institution study design. 5,[7][8][9][10][11] The purpose of this study was to characterize operative and hospitalization-associated risk factors and outcomes including mortality associated with PE using a nationally representative pediatric cohort. We hypothesize that factors such as CVC placement and operation type are associated with higher in-hospital mortality among children with PE.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for PE in children include malignancy, congenital heart disease, systemic lupus erythematosus, renal disease, trauma, and acquired and inherited thrombophilia [ 2 ]. Submassive and massive pulmonary embolism have previously been reported in the adolescent population, with a majority having predisposing comorbidities [ 3 ].…”
Section: Introductionmentioning
confidence: 99%